Fetomaternal Outcomes of Premature Preterm Rupture of Membranes - Rashid, Sara; Noor, Hibba; Khanum, Shallozan; Tabassum, Samia (Indus Journal of Bioscience Research, 2025)
Background: Premature ruptures of membranes and preterm rupture of membranes can be termed as one among the complex obstetric conditions that occur prior to the gestational age of 37 weeks and before the initiation of labor. It is normally associated with a range of potential harmful outcomes to the health of both the baby and the mother. It contributes to various complications such as infection, bleeding, respiratory distress to the baby, and higher admissions to the intensive care unit. Objective: To determine the fetomaternal outcomes in patients with premature preterm rupture of membranes. Study Design: Descriptive cross sectional study. Duration and Place of Study: This study was conducted from November 2024 to May 2025 in the Department of Obstetrics and Gynecology, MTI/Hayatabad Medical Complex, Peshawar. Methodology: A total of 144 pregnant women aged 18–40 years with gestational age of 28–37 weeks presenting with premature preterm rupture of membranes were included. Maternal and neonatal outcomes were recorded and analyzed using SPSS version 27. Continuous variables were presented as mean ± standard deviation while categorical variables were expressed as frequencies and percentages. Results: The mean age of patients was 27.60 ± 4.73 years and mean gestational age was 33.06 ± 2.30 weeks. Majority of patients 85 (59.0%) were from rural areas. Vaginal delivery occurred in 109 (75.70%) cases while cesarean section was performed in 35 (24.30%) patients. Maternal complications included chorioamnionitis in 16 (11.10%) cases, postpartum hemorrhage in 13 (9.00%) cases, positive high vaginal cultures in 23 (16.00%) cases, endometritis in 8 (5.60%) cases, and maternal sepsis in 8 (5.60%) cases. Regarding neonatal outcomes, preterm birth occurred in 133 (92.40%) cases, low birth weight was recorded in 46 (31.90%) neonates, neonatal intensive care unit admission was required in 62 (43.10%) cases, respiratory distress syndrome was diagnosed in 18 (12.50%) neonates, neonatal sepsis developed in 12 (8.30%) cases, and stillbirths occurred in 9 (6.30%) cases. Conclusion: Premature preterm rupture of membranes is associated with significant maternal and neonatal complications.